KAMPANYE SOSIAL KUDAPAN SEGAR KACANG KOWA ASLI KOTA SURABAYA MELALUI PEMBUATAN FILM DOKUMENTER - Sutikno, Sutikno; Laksono, Yunanto Tri; Agustin, Alda (Universitas 17 Agustus 1945 Surabaya, 2025)
This research aims to explore the effectiveness of documentary film as a social campaign media in introducing and raising public awareness of the traditional snack Kacang Kowa, which is a typical Surabaya culinary product. In the context of modernization and shifting consumption preferences, many local snacks are marginalized by instant and global food products. Through a qualitative approach with a case study method, this research designs, produces, and analyzes the impact of a documentary film themed on local culinary preservation. Data were collected through observations, interviews with businesses and consumers, and questionnaires before and after the screening. The results show that documentary media is effective in building emotional and educational narratives, and is able to increase audience knowledge and interest in Kacang Kowa. The campaign also encouraged community participation in supporting local products. In conclusion, documentary films have the potential to be a strategic tool in social campaigns to preserve Indonesia's culinary culture.